Racial Passing Practiced by Mulattoes: A New Historicist Reading of Nella Larsen’s Passing and Jessie Fauset’s Plum Bun” - Desy Eka Fatmawati (Universitas Gadjah Mada, 2017)
Racial passing practice is the act of passing or disguising as white by mulattoes, and it became a phenomenon during Harlem Renaissance. Harlem Renaissance is an era when African American culture related to arts, literature, and music were greatly celebrated. This era can also be said as the most glamorous and happiest moment for African Americans since the antebellum era. Using two of the prominent racial passing narratives during Harlem Renaissance: Passing by Nella Larsen and Plum Bun by Jessie Fauset, this research aims to find the depiction of racial passing practice in the two narratives in order to get deeper understanding of the issue. This research is under American Studies paradigm of Post-nationalist to take into account the minorities’ perspective in understanding America. The minorities’ perspective in this context is from African American’s mixed raced descents (mulattoes). As the focus of this research is historical phenomenon, this research also applies New Historicism as an approach. Based on the analysis, racial passing practice was a reaction from white’s domination through Jim Crow laws, and African Americans considered racial passing practice as a form of both “fooling the white folks” and a betrayal to their “true people”. Keywords: Racial Passing, Mulattoes, Harlem Renaissance, Jim Crow, New Historicism